The ACE2-Ang-(1-7)-Mas Axis and Cardioprotection - S. Santos, Robson A.; B. Pinheiro, Sergio V.; Ferreira, Anderson J. (Current Cardiology Reviews, 2007)
It is well known that the renin-angiotensin system (RAS) is a crucial regulator of the cardiovascular system playing an important role in the control of blood pressure and cardiac function. The relevance of the RAS in cardiovascular diseases is illustrated by the efficiency of RAS blockade to improve survival and cardiac function in patients with heart failure. Emerging evidence suggest that, at least, part of the benefits observed with the use of angiotensin-converting enzyme inhibitors (ACEi) and AT1 receptor blockers (ARBs) could be attributed to the increased Ang-(1-7) levels observed during administration of these agents. Moreover, several experimental studies in animal models of cardiomyopathies have demonstrated that Ang-(1-7) can exert its effects through direct effects produced by ligation to its recent identified Gprotein coupled receptor Mas or indirectly through ACE or AT1 receptors-related mechanisms. The identification of the novels components of the RAS, ACE2 and Ang-(1-7) receptor Mas, provided essential elements for considering the existence of a vasodilator arm of the RAS, represented by the ACE2-Ang-(1-7)-Mas axis. This review briefly highlights the Ang-(1-7) effects in the heart, paying special attention to emerging data suggesting its cardioprotective actions in several cardiomyopathies with focus on the possible role of the ACE2-Ang-(1-7)-Mas axis. In addition, we will discuss the relationship between Ang-(1-7), SRA blockers, and the kallikrein-kinin system.
Keywords: angiotensin-converting enzyme 2